Sentiment Analysis of Depression Detection on Twitter Social Media Users Using the K-Nearest Neighbor Method - Arianti Primadhani Tirtopangarsa; Warih Maharani (Seminar Nasional Informatika (SEMNASIF), 2021)
Every day, millions of people suffer from depression and only a small percentage of them receive proper treatment. Depression is one of the most common mental health disorders. Mental health is very important for humans as well as physical health in general. Not infrequently media users often provide information about themselves and the complaints they experience on burdensome social media. At this time the detection can be detected from the activities of social media users themselves. Because, not infrequently Twitter social media users often provide information about themselves and the complaints they are experiencing on Twitter social media which is burdensome. Therefore, social media Twitter is an option to detect the level of mental health that is being experienced by someone. In this study, the author aims to analyze the application of the K-Nearest Neighbor method in detecting depression in Twitter social media users and see the accuracy value. Based on tests on the KNN classification using the stages of the confusion matrix, the accuracy obtained is 78.18%.